THE EFFECTIVENESS OF MODERN DRESSINGS ON CHRONIC WOUND HEALING: A LITERATURE REVIEW - Talib, Eka; Maane, Marwan Sulistiawan; Riman, Riman; Sulasti, Devi; Anastazya, Ade Masayu Dwi; Islaeli, Islaeli (PT. Nursing Genius Care, 2025)
Background: Chronic wounds, such as diabetic foot ulcers, are a serious health problem with increasing prevalence and risk of complications like infection and amputation. Modern wound dressing, as an innovative approach, is considered effective in creating an optimal moist wound environment to accelerate healing. Purpose: This literature review aims to analyze the effectiveness of various types of modern dressings on the chronic wound healing process. Methods: Articles were collected from PubMed, Google Scholar, and ScienceDirect databases using the keywords